2021
DOI: 10.1038/s43247-021-00261-0
|View full text |Cite
|
Sign up to set email alerts
|

Old subcontinental mantle zircon below Oahu

Abstract: Our understanding of mantle evolution suffers from a lack of age data for when the mantle geochemical variants (mantle components) developed. Traditionally, the components are ascribed to subduction of ocean floor over Earth history, but their isotopic signatures require prolonged storage to evolve. Here we report U-Pb age results for mantle-derived zircon from pyroxenite xenoliths in Oahu, Hawaii, using laser ablation inductively coupled plasma mass spectrometry and isotope dilution - thermal ionization mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Continental zircon grains in Galápagos lavas could indicate the presence of a component of recycled continental crust in the mantle below the islands, in line with geochemical evidence (Blichert-Toft & White, 2001;Hoernle et al, 2000), and similar to Hawai'i where old subcontinental lithospheric mantle zircon below Oahu has been recently reported (Greenough et al, 2021). The inherited zircon population in Galápagos matches, in terms of age and isotope systematics, (a) zircons from exposed basement regions of northern South America and Central America (Heilbron et al, 2017;Nadeau et al, 2013;Noguera et al, 2011), and (b) the inherited zircon grains reported from Cretaceous suprasubduction magmatic arc and mantle rocks of Cuba and Hispaniola recycled in the mantle by subduction of detritus shed from North and South America into nearby oceanic basins (Proenza et al, 2018;Rojas-Agramonte et al, 2016;Torró et al, 2018).…”
Section: Contamination Of the Asthenosphere By Subducted Materialssupporting
confidence: 80%
See 2 more Smart Citations
“…Continental zircon grains in Galápagos lavas could indicate the presence of a component of recycled continental crust in the mantle below the islands, in line with geochemical evidence (Blichert-Toft & White, 2001;Hoernle et al, 2000), and similar to Hawai'i where old subcontinental lithospheric mantle zircon below Oahu has been recently reported (Greenough et al, 2021). The inherited zircon population in Galápagos matches, in terms of age and isotope systematics, (a) zircons from exposed basement regions of northern South America and Central America (Heilbron et al, 2017;Nadeau et al, 2013;Noguera et al, 2011), and (b) the inherited zircon grains reported from Cretaceous suprasubduction magmatic arc and mantle rocks of Cuba and Hispaniola recycled in the mantle by subduction of detritus shed from North and South America into nearby oceanic basins (Proenza et al, 2018;Rojas-Agramonte et al, 2016;Torró et al, 2018).…”
Section: Contamination Of the Asthenosphere By Subducted Materialssupporting
confidence: 80%
“…What all the above mechanisms have in common is that they cannot explain all the data at the same time. Nevertheless, in our opinion one explanation for the presence of zircon grains older than 213 Ma could be the contamination of the asthenosphere by subducted material like in Hawai'i (Greenough et al., 2021), where old xenocrystic zircons possibly reached Oahu by asthenospheric transport after subduction at Papua New Guinea. In the Galapagos' case, a likely geodynamic scenario is that detrital material carrying zircon was brought into the mantle during the West‐directed Cretaceous subduction of the Central Atlantic‐related Proto‐Caribbean ocean beneath the Farallón plate, where the Galapagos plume was likely located (Pindell & Kennan, 2009).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…7A). Such ancient zircons with diverse compositions were also reported from Galápagos (Rojas-Agramonte et al, 2022) and Hawai'i (Greenough et al, 2021) and are best explained as detrital zircons that were brought into the mantle by subduction. Whereas Galápagos is located in the vicinity of a subducted slab in the underlying lower mantle that subducted in the Mesozoic (the Malpelo slab, Van der Meer et al, 2018) no slabs are known below Hawaii and Easter Island.…”
Section: Plio-pleistocene Agesmentioning
confidence: 58%
“…Pilot et al (1998) was the first to report Paleozoic and older zircons from the Central Atlantic mid-ocean ridge. Since this first finding, diverse populations of Paleozoic and older zircons have also again been collected from the Central Atlantic Ridge and reported from the North Atlantic and South Atlantic ridges (Bea et al, 2020;Bjerga & Pedersen, 2021;Bortnikov et al, 2008;Skublov et al, 2022), and recently from intra-oceanic, remote hotspot islands of Hawai'i (Greenough et al, 2021) and Galápagos . These ancient zircons cannot have formed from crystallizing magma at the young mid-ocean ridges, or in the oceanic crust below the hotspot volcanoes, and were consequently interpreted as xenocrysts.…”
Section: Agu Word Manuscript Templatementioning
confidence: 96%